2023
DOI: 10.3390/ma16083039
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Mechanical Behavior of Dry Corn Stalk Cutting

Abstract: This work presents an experimental study of cutting corn stalks for thermal energy generation. The study was carried out for the values of blade angle in the range of α = 30–80°, distance between the blade and the counter-blade g = 0.1, 0.2, 0.3 mm and the velocity of the blade V = 1, 4, 8 mm/s. The measured results were used to determine shear stresses and cutting energy. The ANOVA variance analysis tool was used to determine the interactions between the initial process variables and the responses. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…The findings of Porankiewicz et al (2011) indicated rapid growth in the main force needed with an increase in the entrance angle from 0° to 84.53°, and that a maximum force was required when cutting against the grain. Wilczyński et al (2023) studied the cutting force for corn stalks at different entrance angles, and found that it was significantly impacted by the entrance angle of the circular saw. They reported that as the angle of inclination of a disc cutter increased, the contact and collision area between its non-working surface and the straw increased, resulting in an increased frictional resistance and axial force, ultimately leading to a significant increase in cutting force.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of Porankiewicz et al (2011) indicated rapid growth in the main force needed with an increase in the entrance angle from 0° to 84.53°, and that a maximum force was required when cutting against the grain. Wilczyński et al (2023) studied the cutting force for corn stalks at different entrance angles, and found that it was significantly impacted by the entrance angle of the circular saw. They reported that as the angle of inclination of a disc cutter increased, the contact and collision area between its non-working surface and the straw increased, resulting in an increased frictional resistance and axial force, ultimately leading to a significant increase in cutting force.…”
Section: Introductionmentioning
confidence: 99%